2021
DOI: 10.1177/08971900211022300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Treatment-Dose Enoxaparin Protocol for Patients With Obesity

Abstract: Background: Treatment-dose enoxaparin is not well studied in obese patients. Guidelines suggest that obese patients receiving enoxaparin therapy for acute venous thromboembolism (VTE) should receive a standard initial dose, 1 mg/kg, based on actual body weight. It is possible that this dosing strategy in obese patients may be overestimated, leading to a higher bleeding risk compared to non-obese patients. Objective: To gather data regarding enoxaparin treatment dosing and anti-Xa level monitoring in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When compared to other studies, this study's initial anti-Xa distributions reflected a greater incidence of suboptimal anticoagulation than those seen when defining obesity as a BMI of greater than or equal to 40 kg/m 2 . 12,13 These previous studies identified a correlation between obesity and supratherapeutic anti-Xa levels, leading to an increased risk of bleeding events in their study population. With a median body mass index (BMI) of 35 kg/m 2 in the study cohort, these findings further corroborate the need for dose adjustments according to anti-Xa levels in the obese population.…”
Section: Discussionmentioning
confidence: 91%
“…When compared to other studies, this study's initial anti-Xa distributions reflected a greater incidence of suboptimal anticoagulation than those seen when defining obesity as a BMI of greater than or equal to 40 kg/m 2 . 12,13 These previous studies identified a correlation between obesity and supratherapeutic anti-Xa levels, leading to an increased risk of bleeding events in their study population. With a median body mass index (BMI) of 35 kg/m 2 in the study cohort, these findings further corroborate the need for dose adjustments according to anti-Xa levels in the obese population.…”
Section: Discussionmentioning
confidence: 91%
“…28 Other studies in the obese population have demonstrated the need for reduced doses ranging from 0.7 to 0.8 mg/kg to obtain therapeutic anti-Xa levels. 28-31 In a study by Deal et al, 28 the 6 bleeding events had significantly higher anti-Xa levels (1.5 IU/ml vs 0.98 IU/ml; P = 0.07). A meta-analysis published by Liu et al 32 demonstrated a significantly lower bleeding rate in obese patients using a reduced-dosage strategy than with standard dosing (OR 0.30, 95% CI 0.10-0.89, P = 0.03).…”
Section: Discussionmentioning
confidence: 91%
“…Studies have also used varying definitions of obesity and included different degrees of obesity, making it difficult to compare results between studies. [29][30][31][32][33] While both weight and BMI cutoffs have been used in the literature to define obesity, our study is the first to show an increasing odds of supratherapeutic anti-Xa levels with each category of obesity. BMI may be a better identifier of patients with a higher percentage of adipose tissue than total body weight.…”
Section: Discussionmentioning
confidence: 99%
“…In a large-scale retrospective cohort study, despite receiving chemoprophylaxis, critically ill obese patients had a significantly higher incidence of VTE than nonobese patients ( 3 ). Moreover, for the treatment of obese VTE patients, some researchers have proposed a reduced dosage of LMWH, instead of 1 mg/kg twice daily ( 14 , 15 ). Higher anti-Xa exposure at the same dosage may lead to a higher incidence of supratherapeutic anti-Xa levels.…”
Section: Introductionmentioning
confidence: 99%